Resonant microcavity enhanced infrared photodetectors - Kaniewski, Janusz; Muszalski, Jan; Piotrowski, Józef (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
Resonant cavity enhanced (RCE) infrared photodetectors are used in many applications due to their high quantum efficiency and large bandwidth. Therefore, wide device diversity is desired. In this paper, recent tendencies in design and fabrication of these devices are presented. Various issues for InGaAs/InAlAs/InP RCE detectors operating at 1.55 μm and HgCdTe/CdTe/GaAs RCE devices dedicated for 10.6 μm radiation detection are discussed. The detector structures were grown by means of two industry standard technologies, i.e., molecular beam epitaxy and metaloorganic chemical vapor deposition. Optimized devices can be optically integrated with monolithic microlenses.
Optica Applicata, Vol. 37, 2007, nr 4, s. 405-413
Keywords: optyka; optoelectronic device characterization, design and modeling; III–V and II–VI semiconductors